Rafet Bey: The Last Ottoman Consul in Batavia during the First World War 1911-1924 - Supratman, Frial Ramadhan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
This paper will investigate a brief intellectual history of Rafet Bey, an Ottoman statesman who was appointed as consul-general in Batavia in the early twentieth century. In this paper, intellectual and global history will be the main approach to analyze relations between the Ottomans and the Dutch East Indies (Indonesia) in the early twentieth century, especially during the First World War. The appointment of Rafet Bey as Ottoman consul in Batavia coincided with a moment of strength for the Dutch East Indies, after conquering Aceh and other Indonesian regions. On the other hand, the emergence of the Armenian question also caused some difficulties in Ottoman foreign policy at the time. In short, a brief intellectual biography of Rafet Bey is important because it allows deeper analysis on Ottoman- Indonesia relations in the early twentieth century.DOI: 10.15408/sdi.v24i1.3684